Estimating the value of forests for provisioning non-timber forest products to market: concepts, approaches, and case studies. (April 2020) - Frey, Gregory E.; Chamberlain, James L.; Schmidt, John Paul
Abstract : We discuss the process of estimating the ecosystem service value (ESV) for provisioning of non-timber forest products (NTFPs) to market, with a focus on the United States. NTFPs are harvested throughout the U.S. for numerous purposes, and those sold in market contribute significantly to household and local economies. While estimates of ESV can aid decision-making related to conservation and management, NTFPs have been generally neglected. We discuss challenges and approaches for prioritizing valuation, quantifying production, measuring costs and benefits, and finding data sources. Many NTFP markets are informal, and market players may have an interest in withholding information. Data about geographic and temporal distribution, production cost, quantity harvested, and price may therefore be limited. In two case studies, we explore the nuances of estimating ESV of forests for medicinal products.